Export competitiveness of Ceylon green tea: pre-covid opportunities and challenges - Francis, S.J; Gunathilaka, A.U.G.C.A. (University of Jaffna, 2024)
International trade has opened the doors to many products in the international market for most exporters to mark their dominance on the global level. Green tea, as a value-added tea, is also becoming a demanded product in the market. Only a few countries have increased their competitiveness in that product to a positive trend. In this background, the study aims to identify both competitive and comparative advantages of Ceylon Green Tea in the international market through the competitiveness indexes and insights of experts. This study examines the export competitiveness of Ceylon green tea, focusing on the pre-COVID period. Utilizing secondary data sources, the analysis employs a competitive position framework to evaluate export performance. Key informant interviews (KIIs) were also conducted to gain qualitative insights into market dynamics and strategic challenges. The findings of the descriptive analysis illustrate that Ceylon Green Tea has lost its competitiveness in the past years. Further, identifications of competitive position analysis emphasize that Sri Lanka still has a chance of gaining the comparative advantage of Ceylon Green Tea, especially in terms of the product HS code 090220 of Ceylon Green Tea which has comparatively engaged in the last decade in the global market. The rise of other Asian countries for green tea can also be identified as a reason for declining the export share of green tea. Therefore, Sri Lanka needs to enhance its share in the market to compete with them. The main reasons behind the declining trade value of green tea in Sri Lanka are the issues of exporters and lack of strategic enhancement of the sector as per the experts in the sector. This study also attempted to identify those backdrops and will recommend some steps to be taken for the improvement of the sector.
Keywords: Competitiveness; Comparative Advantage; Export share; Global market; JEL Classification: D41, F10, F14, M3